Impact of the evolution in RAS mutation analysis in Australian patients with metastatic colorectal cancer. Issue 5 (24th January 2022) - Chong, Chia Yuen; Jalali, Azim; Wong, Hui Li; Loft, Matthew; Wong, Rachel; Lee, Margaret; Gately, Lucy; Hong, Wei; Shapiro, Jeremy; Kosmider, Suzanne; Tie, Jeannie; Ananda, Sumitra; et al.
Abstract: Background: RAS mutation testing now routinely informs the optimal management of metastatic colorectal cancer (mCRC), specifically the finding of a RAS mutation defines patients who will not benefit from treatment with an epidermal growth factor receptor inhibitor. Over time more RAS genes have been tested and more sensitive techniques used. Aims: To review routine care RAS testing and results over time. Methods: A retrospective analysis of the molecular data collected prospectively in the multi‐site Treatment of Recurrent and Advanced Colorectal Cancer (TRACC) registry from 2009 to 2018 was undertaken. Patients with RAS data were further analyzed. In parallel, the RAS mutation status of patients enrolled in the Test Tailor Treat (TTT) program was examined for 2011–2018. Results: Of 2908 patients in the TRACC registry, 1892 (65%) were tested, with 898 (47%) of tested patients found to be RAS mutant (RASmt). RAS data were available for 5935 TTT patients. Of the tested TRACC patients diagnosed in 2009 and 2010, 38% were RASmt. For each 2‐year period from 2011/2012 through to 2017/2018, the prevalence of RASmt in TRACC and TTT was 42% and 40% (2011/2012), 52% and 40% (2013/2014), 47% and 49% (2015/2016), and 47% and 49% (2017/2018). Conclusions: Based on both TRACC and TTT data, the proportion of patients reported to have a RAS mutation increased from 2009 to 2015 but has remained relatively stable in recent years. The increased proportion of RASmt patients observed over time is likely largely driven by the uptake of extended RAS testing.